Implementasi Augmented Reality Untuk Media Promosi Program Gaya Hidup Sehat di Santiana Nutrition Club Menggunakan Metode MDLC - Asep Deddy Supriatna; Erika Puspa Dewi (Institut Teknologi Garut, 2026)
Driven by the need for more effective promotion at Santiana Nutrition Club (Santiana NC), this study aims to design and develop an Augmented Reality (AR) application as a promotional tool for healthy living programs at Santiana Nutrition Club (Santiana NC) using the Multimedia Development Life Cycle (MDLC) method, which includes the concept, design, content collection, application development, testing, and distribution phases. The application was developed to provide more interactive promotions compared to conventional methods. Testing was conducted via Black Box Testing to ensure the system functions properly, followed by Alpha Testing by the developers and Beta Testing using the System Usability Scale (SUS) with Santiana NC customers and owners. The test results showed that all features functioned optimally with a SUS score of 72.67, which falls into the “good” category; thus, the application was deemed suitable for use as an effective and easily accessible interactive promotional medium for the public.